Tufted Carpet - Textile Fibers, Dyes, Finishes, and Processes - Moody, Von (William Andrew Publishing, 2011)
Professionals and technicians throughout the entire carpet industry (and suppliers of the industry as well) will find this book invaluable to their activities.